Mecanismos fisiológicos porta-enxertos de citros sob copa de laranja ‘Pêra’ em condições de déficit hídrico - Ferreira, Rivani Oliveira (2019)
Citrus producing areas in Bahia are predominantly distributed in the Coastal Trails zone, which is characterized by a poor distribution of rainfall throughout the year. Among the alternatives to deal with this climatic feature is the use of tree crown combinations that are more tolerant to water deficit. Different attributes can be used as indicative of the greater or lesser resistance of the plants to the water deficit, including the determination of the physiological Murcha point of the species, as well as photosynthetic attributes. Thus, the present work sought to understand the physiological responses of different citrus rootstocks, grafted under "Pêra" orange cup in front of the soil water restriction. The research consisted of two parts, one in a greenhouse, in the experimental unit of Uefs, in the Horto Florestal and the other in the Fazenda Lagoa do Coco, in the municipality of Rio Real-BA, in an experimental block formed by a citrus orchard, deployed in Distrocoeso Yellow Argissolo. In both experiments the 'Pêra' orange cup was grafted on 'Cravo Santa Cruz' lemon, 'Volkameriano' lemon, 'Sunki Tropical' tangerine, 'Cleopatra' tangerine and Citradarin Índio ('TSK x TRENG 256'). In the greenhouse, the experiment consisted of the determination of the physiological wilting point by two methods, the conventional one proposed by Briggs & Shantz, (1912) and another using the method by watering. At the Lagoa do Coco Farm, the experiment consisted of soil water monitoring, from time-reflectometry-TDR with probes at five depths, monthly evaluation of the photosynthetic rates using the infra-red gas analyzer (IRGA), the potential and the chlorophyll content determined by two methods: a portable chlorophyllometer apparatus, a Falker model and the direct method, using Dimethylsulfoxide-DMSO as an extractor, using the Sholander chamber on branches harvested in the middle third of the plant in the early morning hours and the chlorophyll content determined by two methods: and reading by the spectrophotometer at two wavelengths 649 and 665 nm. The minimum values of water at the permanent wilting point were observed in the volcanic lemon (0.0371 m3m3), which also showed high values at the photosynthetic rates being Ci, gs and A (102.11 μmol m -2 s -1; , 11 mmol of H2O m-2 s-1 and 10,13 μmol of CO2 m-2 s-1), respectively, indicating that it is suitable for water deficit situations. The correlation values between chlorophyll content by direct and indirect method showed correlations higher than 0.80 for clh a and total and above 0.47 for chl b, indicating the use of the apparatus in the analysis of chlorophyll in citrus.